From tourist motivations to buying decisions: A multilevel engagement perspective - Nusair, Khaldoon; Okumus, Fevzi; Karatepe, Osman M.; Alfarhan, Usamah F.; de Larrea, Gabriela Lelo (Elsevier, 2023)
This paper offers theoretical and practical implications regarding digital media content generated on social media networks (SMNs). However, limited research has been conducted on this topic, resulting in important knowledge gaps. To narrow this gap, this paper proposes a theoretical framework that explored an important tourist-based antecedent (involvement) and its first- (engagement levels), second- (brand love), third-tier (buying decision) consequences, respectively. Data were gathered from a sample of 722 US tourists who used SMNs for leisure travel purposes. Our findings reported that affective involvement had a strong positive relationship with the three levels of engagement. Additionally, cognitive involvement was significantly related to two engagement levels: consumption and creation. Our findings verified the positive link between the three levels of engagement and brand love. Interestingly, brand love exerted a significant positive impact on both impulse buying and crossbuying decisions. Finally, gender moderated the link between brand love and the cross-buying decision.
Keywords: Brand love; Cross-buying; Involvement; Impulse buying; Multilevel engagement; Social media in tourism